Empowerment of academic staff :a case study at a public institution of higher learning in Sarawak, Malaysia - Kuan, Siaw Vui (2001)
The purpose of this study is to determine the degree of empowerment of academic staff in UITMCSwak Samarahan Campus and the factors that influence empowerment. Hence, the objectives of this study are first of all, to determine whether there is any significant difference among academic staff with varied demographic characteristics, namely, gender, age, race, academic qualification, length of service, status, and responsibility held in terms of empowerment.